2011
DOI: 10.1108/17566691111115117
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of the service environment in forming customer's service experience

Abstract: PurposeThe aim of this paper is to identify and describe important dimensions of the service process as defined by customers, and to compare the results from a specific use context with the recent conceptualization of the experience room.Design/methodology/approachPublic transport travellers were provided with a public transport travel diary and were encouraged to make detailed notes about their service experience during their journey. The diaries were than transcribed and coded in NVivo8 using a constant comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 29 publications
5
49
0
Order By: Relevance
“…From the perspective of delight as a surprise (Oliver, 1997), one can interpret the results to show customer interaction as an element that the customer cannot anticipate, compared to other standard aspects of services, including physical environment and interaction with staff. These findings are consistent with previous studies that identified the role of various dimensions of customer experience on customer delight and satisfaction (Ariffin & Yahaya, 2013;Cetin & Dincer, 2014;Ladhari, 2009;Pareigis et al, 2011;Walls et al, 2011). The results provide new insights into the concepts of consumer delight, satisfaction and loyalty, contributing towards calls in the literature to understand better the influence of both cognitive and affective drivers Loureiro et al, 2014;Oliver et al, 1997).…”
Section: Theoretical Implicationssupporting
confidence: 92%
See 1 more Smart Citation
“…From the perspective of delight as a surprise (Oliver, 1997), one can interpret the results to show customer interaction as an element that the customer cannot anticipate, compared to other standard aspects of services, including physical environment and interaction with staff. These findings are consistent with previous studies that identified the role of various dimensions of customer experience on customer delight and satisfaction (Ariffin & Yahaya, 2013;Cetin & Dincer, 2014;Ladhari, 2009;Pareigis et al, 2011;Walls et al, 2011). The results provide new insights into the concepts of consumer delight, satisfaction and loyalty, contributing towards calls in the literature to understand better the influence of both cognitive and affective drivers Loureiro et al, 2014;Oliver et al, 1997).…”
Section: Theoretical Implicationssupporting
confidence: 92%
“…Various studies have demonstrated empirically that physical environments can elicit positive or negative emotions and satisfaction from customers (Bitner, 1992;Ladhari, 2009;Pareigis, Edvardsson, & Enquist, 2011). A service setting's physical environment comprises a variety of elements, including design and ambient factors such as color, air, scent, illumination, facilities and layout (Baker, Grewal, & Parasuraman, 1994;Han & Ryu, 2009;Lin & Liang, 2011).…”
Section: Impact Of Physical Setting On Delight and Customer Satisfactionmentioning
confidence: 99%
“…The choice of consumption emotions is more specific, narrower and less powerful than the choice of all other probable emotional responses (Han & Back, 2007). Pareigis, Edvardsson, and Enquist, (2011) defined consumption emotions in dissimilar emotional proportions for example enthusiastic and peaceful emotions and enjoyable and unenjoyable emotions. Ali et al (2016) have also described as independent emotions made up of happiness, terror or anger and so on.…”
Section: Guest Emotionsmentioning
confidence: 99%
“…He further remarked that the perceived servicescape may elicit cognitive, emotional, and physiological responses related to the past experience of the customers. Pareigis et al (2011) also discussed factors including physical artefacts, intangible artefacts, technology, customer placement, customer involvement, and interaction, which constitute experience with employees. Among these factors, researchers have focused more on placement and involvement of customers, and their ability to interact with staff as well as technology.…”
Section: Factors Influencing Customer Experiencementioning
confidence: 99%